The Gap between Theory and Practice of Islamic Character Education in Islamic Religious Education (PAI) at State Elementary School Sukasari: Analysis of Contemporary Issues and Challenges - Sarbini Sarbini; Saca Suhendi; Agus Hidayat; Imas Khotimah; Mugeni Muhammad; Nur Sab’rina Fathimah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to explore how Islamic Religious Education (PAI) teachers, students, and other school stakeholders interpret and experience this lack of synchronization in their daily practices. Employing a qualitative case study approach, the research focuses on participants’ subjective experiences and the social processes that shape their understanding of Islamic character education at Sukasari Public Elementary School. Data were collected through in-depth interviews, participant observation, and document analysis, involving eight participants consisting of PAI teachers, students, and the school principal. The data were analyzed using thematic analysis to identify patterns of meaning emerging from classroom interactions, reflections, and social dynamics. The findings reveal three main themes: inconsistency between school culture and the Islamic values being taught, teachers’ moral identity struggles in balancing professional and spiritual demands, and students’ affective dissonance when the values learned do not align with their social experiences. This study contributes theoretically by broadening the understanding of Islamic character education as a relational and emotional process, while also offering practical implications, including the importance of dialogical learning, strengthening school culture, and providing emotional support for both teachers and students. Furthermore, the study opens avenues for future research on moral identity and social dynamics in religious education in Indonesia.